LEADERSHIP OF ISLAMIC EDUCATION ON MTsS MAQAMAM MAHMUDA TAKENGON-ACEH - Ihsan Harun (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The occurrence of clusters of Islamic and general education that developed in the community, a separate problem in the world of education, the other side of the moral decadence of learners to be a problem for parents, so that today madrasah education as one altrenative solution to prevent the problem, answer the challenge in support The quality of Islamic education is very influential on the management of education which is oriented on On Quality, Independence, Partnership and Transparency Management. As well as the leadership pattern in an Islamic educational institution should be a leader beloved by all madrasah stakeholders in particular and generally the wider community. This study used a qualitative approach with field research design. Primary data sources: Head of Madrasah MTs Maqamam Mahmuda Takengon, Head of administrasion system. Secundare source data is written data. The of MTs Maqamam Mahmuda is: Organizing human resources according management to the purpose of the school, Taking decisions on deliberation, tolerating differences in the form of suggestions and actions, mobilizing human resources, using system or rules as a way of thinking, giving confidence in performing their roles and functions, Encouraging creative activities, creating learning schools, implementing agency-based management, empowering schools. While the pattern of Islamic education leadership Mts Maqamam Mahmuda: beloved, trusted, guided, personality and eternal. In other words leadership who put forward the voice of his heart or nature, so that no one hurt in management system.